Research on the Control System for the Conveying and Separation Experimental Platform of Tiger Nut Harvester Based on Sensing Technology and Control Algorithms - Sirui Chen; Jiangtao Qi; Jianping Gao; Wenhui Chen; Jiaming Fei; Hewei Meng; Zhen Ma (Agriculture)
Enhancing the intelligence of Tiger nut harvesting equipment with the advancement of agricultural machinery is imperative. Mismatches between excavation feed rate and conveying-separating capacities hinder the efficiency of Tiger nut harvesters. A visualized Tiger nut harvesting platform was designed to address this, incorporating parameters like conveying speed, torque, vibration frequency, and excavation depth. The platform features a mechanical execution part and an automatic control system with speed, torque, frequency, and depth control modules. Mechanical design analysis defined control parameters and methods for each module. An adaptive B-PID controller was proposed for trajectory tracking, combining backstepping and PID. A control model accounting for motion damping and error compensation was derived. Simulink simulations compared B-PID with backstepping controllers, showing B-PID’s robustness and effective trajectory tracking. Actual experiments assessed mechanical-control coordination using relative error metrics. The results showed that the maximum relative error of rotation speed was 3.8%, the maximum relative error of frequency was 3.67%, and the maximum relative error of excavation depth was 1.5%. Correction models for excavation depth and excitation frequency parameters were established. This study offers a theoretical framework to advance the intelligent design of tiger nut harvesting machinery.